A study of self-efficacy in the use of interactive whiteboards across educational settings: a European perspective from the iTILT project - Emily Hillier; Gary Beauchamp; Shona Whyte (Educational Futures)
This paper reports on the preliminary findings of an EU-funded project called Interactive Technologies in Language Teaching (iTILT). The project aims to produce a range of training materials and resources to support teachers using the interactive whiteboard (IWB) in foreign language (FL) teaching. The project involves 7 European countries (Belgium, Netherlands, Germany, France, Spain, Wales and Turkey) with teachers at differing levels of IWB implementation and proficiency, and encompasses a wide range of educational sectors from primary through to higher education. During the initial stages of data collection, teachers involved in the project completed a likert-scale questionnaire relating to their self-efficacy with both general ICT skills and using a range of IWB features/tools. Despite the differing educational sectors and IWB experience amongst the teachers within the project, there was very little variation in responses between the different countries. Overall, teachers reported high levels of general ICT self-efficacy but low levels of self-efficacy with particular features and tools of the IWB. Nevertheless teachers stated that they allowed pupils to use the IWB and remained positive about the potential benefit of using IWBs to increase pupil participation, engagement and motivation. The findings are considered in the context of existing IWB transitional frameworks and implications for teaching in a variety of classroom contexts are discussed.